Social movement against corruption: Evaluating the contribution of Transparency International Bangladesh (TIB) - Mahjabeen, Tanha (Curtin University, 2014)
Addressing corruption requires active public participation. Transparency International Bangladesh (TIB) strives to mobilize Bangladeshi citizens in an anti-corruption social movement. This research explores TIB’s activities (research, communication and engagement) and investigates their achievements. The study finds that besides building capacity among stakeholders, TIB creates a unique trustworthy brand among people. Potential issues triggered by over-expectation, discontinuity and expanding the scope of work are identified and recommendations are made to facilitate TIB’s resilience and efficiency.